Konsep ‘Sakit Berkepanjangan’ Sebagai Hak Untuk Mengajukan Permohonan Grasi Berdasarkan Alasan Kemanusiaan dan Keadilan - Yuvina Ariestanti (Faculty of Law, Universitas Airlangga, 2021)
AbstractThe large number of prisoners who are elderly and experiencing illness in Indonesia, making the legislators through the Clemency Law add a special reason for granting Clemency. The reasons for Humanity and Justice are added reasons for filing a pardon by the Minister of Justice and Human Rights if the prisoner is in the condition of: 1) children; 2) >70 years old; 3) prolonged illness. Of the several conditions that have been regulated, the condition of